1990
DOI: 10.1002/nme.1620300602
|View full text |Cite
|
Sign up to set email alerts
|

A hyperelastic‐based large strain elasto‐plastic constitutive formulation with combined isotropic‐kinematic hardening using the logarithmic stress and strain measures

Abstract: This paper addresses the formulation of a set of constitutive equations for finite deformation metal plasticity. The combined isotropic-kinematic hardening model of the infinitesimal theory of plasticity is extended to the large strain range on the basis of three main assumptions: (i) the formulation is hyperelastic based, (ii) the stress-strain law preserves the elastic constants of the infinitesimal theory but is written in terms of the Hencky strain tensor and its elastic work conjugate stress tensor, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
191
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(192 citation statements)
references
References 23 publications
1
191
0
Order By: Relevance
“…This coupled constitutive model is implemented in the hyperelastic large strain framework in a corotational formulation with the total Lagrange formalism, which was shown to be easily implemented in finite element codes (Eterovic and Bathe, 1990;Cuitino and Ortiz, 1992). The modeling strategy involves the following elements:…”
Section: Introductionmentioning
confidence: 99%
“…This coupled constitutive model is implemented in the hyperelastic large strain framework in a corotational formulation with the total Lagrange formalism, which was shown to be easily implemented in finite element codes (Eterovic and Bathe, 1990;Cuitino and Ortiz, 1992). The modeling strategy involves the following elements:…”
Section: Introductionmentioning
confidence: 99%
“…For the isotropic elastic stress-strain law it can be shown that [1,4]: with the following stress expressions which follow from the dissipation inequality…”
Section: Constitutive Frameworkmentioning
confidence: 99%
“…where f , f are the yield functions defined respectively in the spatial and the rotated descriptions, b E is the elastic Finger tensor, L v means the Lie derivative,γ ,λ are consistency parameters (the flow tensors are taken as unitary) and β, B are the back stresses in the spatial and rotated configurations respectively [4], i.e.,…”
Section: Constitutive Frameworkmentioning
confidence: 99%
See 2 more Smart Citations